Two new species of the genus Ficobracon van Achterberg and Weiblen (Hymenoptera: Braconidae) from China, expanding its host range - Wei, Pan; Achterberg, Cees Van; Feng, Gui; Xiao, Hui; Huang, Da-Wei (Zootaxa, 2013)
Syconia of figs (Moraceae: Ficus spp.) harbour many wasp species, mostly belonging to several genera of chalcidoids (Hymenoptera: Chalcidoidea). In contrast, only two genera of Braconidae (Hymenoptera: Ichneumonoidea) with a few known species are found in syconia belonging to the subgenus Urostigma. The braconid fig wasps have an infrequent oc-currence with low population density and are rarely encountered. Two new species, Ficobracon rhiknosus sp. nov. from figs of the subgenus Urostigma, and F. codonatus sp. nov. from figs of the subgenus Sycidium are described. Our previous experiments firmly support the suggestion that the Ficobracon species are parasitoids of non-pollinating chalcidoid fig wasps in the syconia.